Karakteristik Penggunaan Ruang dan Strategi Spasial Home-Based Enterprise dalam konteks Informalitas - Rivandi, Pascal (ARSITEKTURA, 2021)
Home-Based Enterprise as one type of informality in urban area with home as the main resource. This paper analyses home-based enterprises focusing on identifying characteristics of spatial use in Home-Based Enterprise which is divided into three type of bussiness, production, service and sales. The characteristics spatial use of the three types of Home-Based Enterprise, are very different and will determine spatial strategies in HBE development. Spatial strategy is a step to develop Home-Based Enterprise, through an adaptive strategy consisting of adaptation strategy by sharing, adaptation strategy by extending and adaptation strategy by shifting. The case study method conducted in making this paper is qualitative by describing characteristics of spatial use concerning on the home-based enterprises and spatial strategies based on the three types of Home-Based Enterprise. It is concluded that there is a relationship between the characteristics of spatial use and spatial strategies in the development of Home-Based Enterprise.